A Q methodology approach to the evaluation of land administration mergers - Muparari, Tsitsi N.; De Vries, Walter Timo; Zevenbergen, Jaap (Midlands State University, 2018)
Paper presented at ICGELA 2018: 20th International Conference on Geomatics Engineering and Land Administration, At Mumbai on February 22-23 2018